2010
DOI: 10.1093/ndt/gfq416
|View full text |Cite
|
Sign up to set email alerts
|

Renal impairment, hypertension and plasma urotensin II

Abstract: These data suggest a potential vasodilatory role of UII in humans with kidney disease or hypertension. The reduction in UII levels in CKD also suggests either reduced production or greater clearance, or both, of UII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 48 publications
(58 reference statements)
5
23
0
2
Order By: Relevance
“…We found that UII is significantly lower in our current study, and this is consistent with Mosenkis, et al's results [18] but differs from that of Tostune, et al [8,9]. The reduction in UII levels in hemodialysis patients can suggest reduced production, greater clearance, or both [18]. On the other hand, some authors believed that the difference of UII levels can be a result of using different antibodies for the UII BIA assessment (such as anti-UII polyclonal antibody or anti-UII monoclonal antibody) [18].…”
Section: Multiple Regression Analysis Of Circulating Irisin With Othesupporting
confidence: 93%
See 2 more Smart Citations
“…We found that UII is significantly lower in our current study, and this is consistent with Mosenkis, et al's results [18] but differs from that of Tostune, et al [8,9]. The reduction in UII levels in hemodialysis patients can suggest reduced production, greater clearance, or both [18]. On the other hand, some authors believed that the difference of UII levels can be a result of using different antibodies for the UII BIA assessment (such as anti-UII polyclonal antibody or anti-UII monoclonal antibody) [18].…”
Section: Multiple Regression Analysis Of Circulating Irisin With Othesupporting
confidence: 93%
“…Some studies observed a lower UII concentration among subjects with CKD and ESRD whereas other studies reported higher UII concentration in patients with kidney disease [16,17]. We found that UII is significantly lower in our current study, and this is consistent with Mosenkis, et al's results [18] but differs from that of Tostune, et al [8,9]. The reduction in UII levels in hemodialysis patients can suggest reduced production, greater clearance, or both [18].…”
Section: Multiple Regression Analysis Of Circulating Irisin With Othesupporting
confidence: 88%
See 1 more Smart Citation
“…However, some other studies have demonstrated a lack of any significant difference between patients with and without hypertension (19). Mosenkis et al (27) refuted the presence of a correlation between UII level and blood pressure. Despite all of these reports, the effects of antihypertensive treatments on UII levels have not been investigated so far.…”
Section: Discussionmentioning
confidence: 98%
“…Erbay ve arkadaşları da son yıllarda yaptığı bir ça-lışmada [66] serum ÜT 2 seviyelerini non diaper hipertansiyonlu hastalarda diaper hipertansiyonlu hastalardan daha yüksek bulmuşlar ve yüksek ÜT 2 seviyelerinin hastalığın kötü prognozundan sorumlu olabileceğini söylemişlerdir. Mosenkis ve arkadaşları ise son yıllarda yaptığı bir çalışmada [67] ÜT 2'nin böbrek hastalıkları ve hipertansiyonda güçlü vazodilatör rolünün olduğunu savunmuşlar ve ÜT 2 artışının artmış üretim veya artan klirensten veya ikisinden olabileceğini söy-lemişlerdir. Bai ve arkadaşları da son yıllarda peritoneal diyaliz hastalarında yaptığı bir çalışmada [68] ÜT 2'yi normal sistolik kan basıncı olan hastalarda yüksek sistolik kan basıncı olan hastalara göre yüksek, normotansif yüksek volümlü hastalarda da hipertansif yüksek volümlü hastalara göre yüksek bulmuşlar-dır ve ÜT 2'nin hipertansiyondaki volüm rezistansının patogene zinde yer alabileceğini söylemişlerdir.…”
Section: Sistemik Hipertansiyonunclassified